A case of combined parasitism of a redfish (Sebastes marinus) by nematodes and copepods - KATZAGIANNAKIS, I.; FRAGKIADAKIS, G.; KARATASOU, A.; ASKOXILAKI, i.; BERLAND, B. (Journal of the Hellenic Veterinary Medical Society, 2018)
NO ABSTRACT